First record of leucism in Glossophaga soricina valens (Phyllostomidae: Chiroptera) from Peru - Ruelas, Dennisse; Sánchez, Miluska; Molina, Mercedes; Pacheco, Víctor (THERYA, 2016)
Leucism is a genetic condition that manifest as the total or partial lack of coloration, as result of a deficiency in the melanin deposit in the skin and fur. We present the first occurrence of leucism in Glossophaga soricina valens from Peru, a nectarivorous species of the western slope of the Andes from Peru and Ecuador, and the Marañon valley. Also, we discuss some implications of this occurrence, and update the checklist of bat species recorded with leucism in the America.